Epidemiology of sepsis in AUSL Romagna and time to positivity - Anna Marzucco; Michela Fantini; Maria Sofia Montanari; Giulia Gatti; Martina Manera; Maria Vittoria Tamburini; Manuela Morotti; Agnese Denicolò; Francesco Congestrì; Valentina Arfilli; Pasqua Schiavone; Alessandra Scagliarini; et al. (Microbiologia Medica, 2024)
Not available.